2010
DOI: 10.1073/pnas.1016962108
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to discodermolide, a microtubule-stabilizing agent and senescence inducer, is 4E-BP1–dependent

Abstract: Discodermolide is a microtubule-stabilizing agent that induces accelerated cell senescence. A discodermolide-resistant cell line, AD32, was generated from the human lung cancer cell line A549. We hypothesize that the major resistance mechanism in these cells is escape from accelerated senescence. AD32 cells have decreased levels of 4E-BP1 mRNA and protein, relative to the parental discodermolide-sensitive A549 cells. Lentiviral-mediated re-expression of wild-type 4E-BP1 in AD32 cells increased the proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…36 Discodermolide is a microtubule-stabilizing agent that induces accelerated cell senescence, and it has recently been shown that reintroduction of 4E-BP1 even a nonphosphorylatable mutant (Thr-37/46 Ala) of 4E-BP1 can revert the resistance of the 4E-BP1-defective cancer cells to discodermolide via restoration of induced accelerated senescence. 37 Our data here showed that depression of 4E-BP1 sensitized HepG2 cells to paclitaxel, and which is partially attributed to the increased induction of apoptosis. Although depletion of 4E-BP1 also sensitizes HeLa cells to paclitaxel, no significant apoptosis was induced in response to paclitaxel treatment even with the knowdown of 4E-BP1.…”
Section: Discussionmentioning
confidence: 51%
“…36 Discodermolide is a microtubule-stabilizing agent that induces accelerated cell senescence, and it has recently been shown that reintroduction of 4E-BP1 even a nonphosphorylatable mutant (Thr-37/46 Ala) of 4E-BP1 can revert the resistance of the 4E-BP1-defective cancer cells to discodermolide via restoration of induced accelerated senescence. 37 Our data here showed that depression of 4E-BP1 sensitized HepG2 cells to paclitaxel, and which is partially attributed to the increased induction of apoptosis. Although depletion of 4E-BP1 also sensitizes HeLa cells to paclitaxel, no significant apoptosis was induced in response to paclitaxel treatment even with the knowdown of 4E-BP1.…”
Section: Discussionmentioning
confidence: 51%
“…The investigators then showed that a subset of cells were able to escape senescence and that those escaping cells were more resistant to chemotherapeutics than the parental cells. Further support for this idea was reported by Chao et al (Chao et al, 2011) when they found that resistance to the microtubule-stabilizing agent Discodermolide in a subset of lung carcinoma cells was linked to the emergence from senescence and possibly mediated by alterations in the expression of 4E-BP1. The different escape routes observed might suggest that each cell population invokes unique mechanisms that allow for breaking senescence.…”
Section: Therapy Resistance and Breaking Senescencementioning
confidence: 59%
“…Ten cell lines were used in this study as detailed: MDA-MB-468, BT20, HCC1143, HS578T, BT549, MDA-MB-157 (TNBC breast), MCF7 (ER+ breast), HEY (serous ovarian), A549, and its (+)-discodermolide-resistant variant, AD32 2 (K-RAS mutant NSCLC). All cell lines were purchased from the American Type Culture Collection, unless otherwise stated, and maintained in RPMI medium (HyClone) supplemented with 10% fetal bovine serum (Gibco).…”
Section: Methodsmentioning
confidence: 99%